1975
DOI: 10.1085/jgp.65.4.527
|View full text |Cite
|
Sign up to set email alerts
|

A synthetic strand of cardiac muscle: its passive electrical properties.

Abstract: A B S T R n O T The passive electrical properties of synthetic strands of cardiac muscle, grown in tissue culture, were studied using two intraeeUular microelectrodes: one to inject a rectangular pulse of current and the other to record the resultant displacement of membrane potential at various distances from the current source. In all preparations, the potential displacement, instead of approaching a steady value as would be expected for a cell with constant electrical properties, increased slowly with time … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
20
2

Year Published

1978
1978
2014
2014

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(25 citation statements)
references
References 50 publications
(71 reference statements)
3
20
2
Order By: Relevance
“…Radial non-uniformities in concentration occur more readily because of the disparity in the potassium transport numbers of the cleft membrane and the cleft fluid. In view of the sensitivity of the depletion current measurement, it would be interesting to look for depletion currents in cultured cardiac preparations (Lieberman, Sawanobori, Kootsey & Johnson, 1975, Sachs, 1975 when comparing them to the rabbit Purkinje fibre.…”
Section: Discussionmentioning
confidence: 99%
“…Radial non-uniformities in concentration occur more readily because of the disparity in the potassium transport numbers of the cleft membrane and the cleft fluid. In view of the sensitivity of the depletion current measurement, it would be interesting to look for depletion currents in cultured cardiac preparations (Lieberman, Sawanobori, Kootsey & Johnson, 1975, Sachs, 1975 when comparing them to the rabbit Purkinje fibre.…”
Section: Discussionmentioning
confidence: 99%
“…When premature beats are introduced early in the cardiac cycle, however, there is frequently a depolarization that cannot be measured by this conventional method. We therefore employed a template method that is similar to that described by Jongsma and van Rijn (1972) and Lieberman et al (1975) in their studies of the passive membrane properties of cultured heart cells. The template method is illustrated in Figure 2B.…”
Section: Methodsmentioning
confidence: 99%
“…Micropatterned cardiomyocyte cultures attempt to recreate this architecture in vitro, and hence may reproduce more faithfully the true physiological conditions of heart muscle and may be also useful for cell-based sensors and tissue engineering applications. Patterning heart cells in culture to create "cable-like" strands was first performed, without microfabrication techniques, by Lieberman and coworkers, who grew dissociated cells in grooves cut in agar 217,218 or used nylon filaments as substrates. 219 Rohr et al 220 found that neonatal rat heart cells prefer to attach to glass over photoresist, so they used photoresist as the non-adherent material.…”
Section: Micropatterns Of Cardiacmentioning
confidence: 99%